Pengaruh Good Corporate Governance Dan Audit Internal Terhadap Kinerja Keuangan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Properti Dan Real Estate Yang Terdaftar Di Bei Tahun 2018-2022 - Irawan Triprasetyo; Hero Priono (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the effect of good corporate governance and internal audit on financial performance with company size as a moderating variable in property and real estate companies listed on the IDX in 2018-2022. This research was conducted in property and real estate companies because the company's financial performance has tended to decline in recent years. This research uses quantitative methods. The research population was 85 property and real estate companies listed on the Indonesia Stock Exchange in 2018-2022. This study used purposive sampling method, the sample obtained was 40 companies with a total of 200 analysis data. Hypothesis testing using Smart PLS 3.0 software. The results of this study indicate that good corporate governance and internal audit do not contribute to financial performance. Meanwhile, company size has no role in moderating the relationship between good corporate governance and financial performance. In addition, company size also has no contribution in moderating the relationship between internal audit and financial performance.